Host [compact disc, unabridged] - Cook, Robin, 1940- (Penguin Audio, 2015)
"Lynn Pierce, a fourth-year medical student at Mason Dixon University, thinks she has her life figured out. But when her otherwise healthy boyfriend, Carl, enters the hospital for routine surgery, she doesn't know it's the last time she will see him whole again. Devastated by Carl's death, Lynn searches for answers. Convinced there's more to the story than what the authorities are willing to reveal, Lynn uses all her resources at Mason Dixon--including her initially reluctant lab partner, Edward--to hunt down evidence of medical error or malpractice. What she uncovers, however, is far more disturbing. Hospitals associated with Sentinel Healthcare, including the one attached to Mason Dixon, have unnervingly high rates of unexplained anesthetic complications and patients contracting serious and terminal illness in the wake of routine surgery. When Lynn and Edward begin to receive death threats, they know they're into something bigger than either of them anticipated. They soon enter a desperate race against time for answers before shadowy forces behind Sentinel Healthcare can put a stop to their efforts once and for all" --